Lornoxicam use to reduce the pain associated with propofol injection. Issue 1 (1st January 2017) - Başak, Nihal; Aksoy, Yakup; Kaydu, Ayhan; Şahin, Ömer Fatih
ABSTRACT: Aim : To investigate the efficacy of lornoxicam in the prevention of the pain associated with propofol injection. Material and method : Approval for this study was granted by the ethics committee of our hospital. Using a computer randomisation software, 120 patients undergoing elective surgery were assigned to four equal groups. In Group I (control group), immediately before anaesthesia induction, 10 ml of isotonic 0.9% NaCl solution (placebo) was administered intravenously (IV). In Groups II, III and IV, the same injection contained 2 mg, 4 mg and 8 mg of lornoxicam respectively. A tourniquet was then applied to the forearm for two minutes. Pain evaluation was made using a verbal pain score. Results : Differences in pain severity scores were statistically significant between Groups I and II, Groups I and III, Groups I and IV and between Groups II and III (p < 0.05). However, no significant difference was determined between Groups III and IV (p = 0.401). Conclusion : In all groups administered with lornoxicam, there was a significant reduction in the severity of pain associated with propofol injection, in comparison with the control group. Maximum effect is obtained with a dose of 4 mg.